Furnace ecology - S. L. Rovin; L. E. Rovin; L. N. Rusaya; O. V. Gerasimova (Литьë и металлургия, 2018)
The article studies the issues of dust and gas cleaning of emissions from smelting units, the analysis of the relationship of furnaces energy efficiency and their environmental parameters, the complex systems that insure high efficiency of gas purification which are aspirated from the melting units are provided, with minimal energy and investment costs.